Thermal Effect of Circulating Bath Water Running onto the Neck and Shoulders - NOMURA, Ryoko; SHIMIZU, Yuki; NAKAGAWA, Kota; YAMAMOTO, Junpei; NAKAGAMI, Sotaro; WATANABE, Kei; NAKAJIMA, Kazuki (INTERNATIONAL JOURNAL OF AFFECTIVE ENGINEERING, 2025)
Bathing has various beneficial effects, including immune function strengthening, muscle fatigue recovery, and sweating function recovery. Furthermore, full-body bathing exerts a particularly significant thermal effect. In recent years, bathtubs equipped with a circulating bath water system have been developed as a means of increasing this thermal effect. However, few studies have investigated the thermal effect of bathing while running hot water over the neck and shoulders using a circulating bath water system. Thus, this study examined the thermal effect of circulating bath water running onto the neck and shoulders, and compared the effects with those of plain hot water bathing. Core body temperature and sweat rate were significantly increased using the circulating bath water system compared with bathing in plain hot water. Our findings suggest that circulating bath water on the neck and shoulders provides a strong thermal effect.